Multi Frequency on RGB Lighting LED Driver Technique - Jirawath Parnklang; Lalita Phikunthong; Rawisara Jantri; Pichkanit Sukpasri (My University, 2020)
Abstract In this paper, we conducted RGB incident light intensity of the high power white lighting LED. The current control 50% duty cycle pulse signal source with appropriate semiconductor carrier frequency response are supply to the RGB white lighting LED. Although, the carrier relaxation time of the red blue and green light in the white lighting LED are not the same value which depend on the carrier different of the energy level. The measurement show that the lowest duty cycle appropriate pulse signal for only blue or UV base white LED give more relative light intensity than normal (low frequency) signal within 11%.
Keywords: Duty cycle; RGB color model; SIGNAL (programming language); LED lamp; Dimmer; Gas Sensing Nanomaterials and Sensors